P Pelatihan Grafik Maple dalam Pembelajaran Matematika - Retno Marsitin (Jurnal Pengabdian Barelang, 2020)
Nowadays, the mathematics teachers have to implement mathematics learning using technology, especially for vocational mathematics teachers. Technological applications that can be utilized in learning mathematics include maple. Maple is mathematical software that integrates computational capabilities both symbolic and numerical, graphics are very influential to help in solving mathematical problems. The method offered in solving partner problems is by organizing maple graph training and mentoring in applying maple graphics in mathematics learning. The success of this community service activity is supported by some factors, namely: high interest and desire in participating in training activities to completion, interest and support from Singosari PGRI Vocational School as a partner school in maple graph training activities, active involvement so that there is mutual sharing of knowledge about maple graphics. The community service activity with maple graphic training gets a positive response from vocational teachers with an achievement of 93%, the results of the presentation of maple graphics with very good achievements are 87%. This community service activity with maple graphic training for Singosari Vocational School teachers are very useful in adding insight of computer knowledge, especially the use of maple graphics, and fostering creativity and skills in using maple graphics in mathematics learning.